Enrichment of the Galactic disc with neutron-capture elements: Gd, Dy, and Th. Issue 3 (25th August 2022) - Mishenina, T; Pignatari, M; Gorbaneva, T; Côté, B; Yagüe López, A; Thielemann, F-K; Soubiran, C
ABSTRACT: The study of the origin of heavy elements is one of the main goals of nuclear astrophysics. In this paper, we present new observational data for the heavy r -process elements gadolinium (Gd, Z = 64), dysprosium (Dy, Z = 66), and thorium (Th, Z = 90) in a sample of 276 Galactic disc stars (–1.0 < [Fe/H] < + 0.3). The stellar spectra have a high resolution of 42 000 and 75 000, and the signal-to-noise ratio higher than 100. The LTE abundances of Gd, Dy, and Th have been determined by comparing the observed and synthetic spectra for three Gd lines (149 stars), four Dy lines (152 stars), and the Th line at 4019.13 Å (170 stars). For about 70 per cent of the stars in our sample, Gd and Dy are measured for the first time, and Th for 95 per cent of the stars. Typical errors vary from 0.07 to 0.16 dex. This paper provides the first extended set of Th observations in the Milky Way disc. Together with europium (Eu, Z = 63) data from our previous studies, we have compared these new observations with nucleosynthesis predictions and Galactic Chemical Evolution simulations. We confirm that [Gd/Fe] and [Dy/Fe] show the same behaviour of Eu. We study with GCE simulations the evolution of [Th/Fe] in comparison with [Eu/Fe], showing that unlike Eu, either the Th production is metallicity dependent in case of a unique source of the r-process in the Galaxy, or the frequency of the Th-rich r-process source is decreasing with the increase in [Fe/H].